2023
DOI: 10.1007/s12035-023-03219-9
|View full text |Cite|
|
Sign up to set email alerts
|

A Homozygous PPP1R21 Splice Variant Associated with Severe Developmental Delay, Absence of Speech, and Muscle Weakness Leads to Activated Proteasome Function

Abstract: PPP1R21 acts as a co-factor for protein phosphatase 1 (PP1), an important serine/threonine phosphatase known to be essential for cell division, control of glycogen metabolism, protein synthesis, and muscle contractility. Bi-allelic pathogenic variants in PPP1R21 were linked to a neurodevelopmental disorder with hypotonia, facial dysmorphism, and brain abnormalities (NEDHFBA) with pediatric onset. Functional studies unraveled impaired vesicular transport as being part of PPP1R21-related pathomechanism. To decip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…In fibroblasts from a patient with a splice-site mutation in PPP1R21, immunoblot studies revealed accumulation of autophagy adaptor p62, proteomic analyses revealed an overactivation of the ubiquitin-proteasome system (UPS), and cell morphological measurements indicated spatial rearrangement in the actin cytoskeleton. The authors hypothesized overactivation of the UPS represents an attempt to counteract protein aggregates resulting from endosolysosomal stall and thereby prevent cellular degeneration 7. While we report the first two missense variants in PPP1R21 associated with this recognizable disorder, we did not observe any clear indication of allelism that would account for any milder spectrum of the disorders in a genotype-phenotype spectrum.In conclusion, here we present the clinical, molecular, and radiological features of PPP1R21-related NDD in 11 new subjects with six novel variants and two recurrent variants.…”
contrasting
confidence: 78%
See 4 more Smart Citations
“…In fibroblasts from a patient with a splice-site mutation in PPP1R21, immunoblot studies revealed accumulation of autophagy adaptor p62, proteomic analyses revealed an overactivation of the ubiquitin-proteasome system (UPS), and cell morphological measurements indicated spatial rearrangement in the actin cytoskeleton. The authors hypothesized overactivation of the UPS represents an attempt to counteract protein aggregates resulting from endosolysosomal stall and thereby prevent cellular degeneration 7. While we report the first two missense variants in PPP1R21 associated with this recognizable disorder, we did not observe any clear indication of allelism that would account for any milder spectrum of the disorders in a genotype-phenotype spectrum.In conclusion, here we present the clinical, molecular, and radiological features of PPP1R21-related NDD in 11 new subjects with six novel variants and two recurrent variants.…”
contrasting
confidence: 78%
“…We proposed that null, frameshift, and splicing variants result in complete loss‐of‐function (LoF) while the missense variants result in partial LoF thus behaving as hypomorphic alleles. Previous reports have only reported complete LoF variants (nonsense, frameshift, and splicing variants) 5–9 . Here were report the first two subjects with PPP1R21 missense variant alleles and neurodevelopmental phenotype which along with the other novel variant expand the allelic spectrum of the disease.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations